2023
DOI: 10.1136/jnnp-2022-330158
|View full text |Cite
|
Sign up to set email alerts
|

Decompression alone versus decompression with instrumented fusion in the treatment of lumbar degenerative spondylolisthesis: a systematic review and meta-analysis of randomised trials

Abstract: ObjectiveTo determine the efficacy of adding instrumented spinal fusion to decompression to treat degenerative spondylolisthesis (DS).DesignSystematic review with meta-analysis.Data sourcesMEDLINE, Embase, Emcare, Cochrane Library, CINAHL, Scopus, ProQuest Dissertations & Theses Global, ClinicalTrials.gov and WHO International Clinical Trials Registry Platform from inception to May 2022.Eligibility criteria for study selectionRandomised controlled trials (RCTs) comparing decompression with instrumented fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
1
0
1
Order By: Relevance
“…Whether or not to perform fusion is a controversial issue in treating DLS, where Kaiser et al . 48 found that DO was adequate compared with instrumented fusion. Nevertheless, we found that in open or endoscopic surgery, decompression with fusion (DF and DFI) was superior to DO in improving patient pain, dysfunction, and reoperation rates.…”
Section: Discussionmentioning
confidence: 96%
“…Whether or not to perform fusion is a controversial issue in treating DLS, where Kaiser et al . 48 found that DO was adequate compared with instrumented fusion. Nevertheless, we found that in open or endoscopic surgery, decompression with fusion (DF and DFI) was superior to DO in improving patient pain, dysfunction, and reoperation rates.…”
Section: Discussionmentioning
confidence: 96%
“…Naopak, dekomprese s fúzí prokázala mírně nižší míru reoperací (OR 1,17; tj. o 19 pacientů z 1000 více potřebovalo po prosté dekompresi reoperaci do 2 let) (30).…”
Section: Prostá Dekomprese Vs Dekomprese S Fúzí U Spondylolistéz -Tvo...unclassified